(untitled) (International Journal of Engineering and Computer Science, 2016)
To make the most of network lifetime in Wireless Sensor Networks (WSNs) the paths for data transfer are chosen in a manner that the total energy utilized along the path is minimized. To support high scalability and better data aggregation, sensor nodes are regularly assembled into disjoint, non overlapping subsets called clusters. Clusters create hierarchical WSNs which incorporate efficient utilization of limited resources of sensor nodes and thus extends network lifetime. The goal of this paper is to show a cutting edge review on clustering algorithms reported in the literature of WSNs. This paper presents various energy efficient clustering algorithms in WSNs.